Modelo 3D do círculo arterial do cérebro como ferramenta de ensino da vascularização do Sistema Nervoso Central - Teixeira, Cláudio Silva (2023)
The cerebral arterial circle consists of a circuit of anastomoses located at the base of the skull, responsible for joining the anterior and posterior brain circulations with clinical and surgical importance. Furthermore, it is clear that the use of alternative and modern teaching tools, such as 3D printing, especially for parts that are difficult to access in anatomy laboratories, such as the cerebral arterial circle, can positively impact the learning of human anatomy. Thus, the use of 3D printing in anatomy teaching becomes an important tool in the teaching and learning process. Based on these assumptions, the objective of this work was to investigate the effectiveness of using 3D printed models of the cerebral arterial circle on the learning of medical students. An exploratory, quasi-experimental study with a quantitative approach was carried out. 15 3D models were designed and printed and then distributed to groups of 5 students. In addition, along with each impression, two booklets were given with indications of arterial markings. Students were able to take the parts to study at home and had a face-to-face group study moment with the help of monitors from the Anatomy discipline. To measure learning, structured tests with 15 questions were used before and after using the pieces. For data analysis, the Wilcoxon test was used, with data that presented p<0.05 being considered significant. It was observed that most of the students were female with an average age of 23 years. The average value of correct answers in the pre-test was 3.77±0.2 when compared to the post-test with an average of correct answers of 9.66±0.52. Thus, there was a statistically significant difference p<0.001 in the rate of correct answers, representing a gain of 39.3% in performance compared to the test prior to the use of the part. It was found that the use of 3D pieces to study the arterial vascularization of the central nervous system demonstrated significant learning and improved performance in the test, making it possible to infer that the use of the model contributed positively to the students' learning.